Placentografía radioisotópica - Cabello, Alberto José; Doctorovich, Susana; Diez, Francisco; Placer, Alejandro E. (Sociedad de Obstetricia y Ginecología de Buenos Aires; Argentina, 1968)
Fil: Cabello, Alberto José Comisión Nacional de Energía Atómica; Argentina